FUNDUS AUTOFLUORESCENCE FINDINGS IN EARLY CHLOROQUINE MACULOPATHY. Issue Volume 12:Issues 2(2018) (2018) - Bergholz, Richard; Rossel, Mirjam; Schroeter, Jan; Dutescu, Ralf M.; Salchow, Daniel J.
Abstract : Background/Purpose: Toxic maculopathy is a rare but severe complication of chloroquine intake. Although the phenotype of established maculopathy was analyzed in detail, few data exist on the ophthalmologic findings in the early stage. Methods: The authors present 4 female patients with unequivocal signs of chloroquine maculopathy (bilateral [peri-]central scotoma in the visual fields, structural alterations of the macula in the optical coherence tomography) but normal or atypical findings as to fundus autofluorescence imaging. Results: In all patients, optical coherence tomography showed perifoveal thinning and subtle alterations of the outer retinal layers. In one patient, the latter was limited to the pericentral region, whereas it showed a more diffuse distribution in two other patients. One patient showed a combination of pericentral and diffuse damage. Multifocal electroretinography was recorded in three patients and revealed the typical (peri-)central amplitude reductions. Conclusion: A normal fundus autofluorescence does not rule out toxic maculopathy. Optical coherence tomography and multifocal electroretinography seem to be more sensitive in the early stage of the disease. In case of typical complaints and visual fields, the optical coherence tomography has to be evaluated for subtle alterations of the outer retina. Their presence justifies the cessation of the drug. Multifocal electroretinography may be of special value in these problematic cases. Abstract : The data presented in this article demonstrate the importance of relying on multiple examination methods when screening for chloroquine toxicity. The authors especially emphasize that normal fundus autofluorescence imaging does not rule out the presence of toxic maculopathy. Any ophthalmologist caring for (hydroxy-)chloroquine patients should be aware of this fact.